Magnitude of self-reported non-fatal work-related injuries and associated factors among construction workers in Aleta Wondo, Sidama, Ethiopia - Abel Afework; Aiggan Tamene; Mahlet Gashaw (Scientific Reports)
Abstract Ethiopia has experienced rapid urbanization over the past three decades, leading to the explosion of building construction. The job created in the construction industry of the country was hazardous due to the nature of the activities involved in the industry. However there is paucity of evidence regarding the prevalence and risk factors of injuries in the industry to make evidence-based policy framework within the country. Therefore, this study seeks to examine the magnitude of non-fatal occupational injuries and the associated factors among building construction sites workers in Aleta Wodo, Sidama, Ethiopia. An institutional based cross-sectional study was conducted in South Ethiopia from September to October 2023. The study utilized a multi-stage sampling technique to select the 613 study participants. The data was collected using a structured interviewer administered questionnaire. Epi Inf version 7.2 was used to enter data and the data was analysed using IBM-SPSS version 22. Bivariate and Multivariate logistic regression was conducted to assess association between the outcome and predictor variables. During the multivariable regression p-value less than 0.05 were taken to determine significant association. The annual prevalence of wok-place injury in the current study was 64.1% (95 CI: 60.7, 67.9). Male construction workers [AOR = 3.6, 95% CI (2.12, 6.15)], monthly income of ≤ 1000 [AOR = 4.56, 95% CI (1.56, 13.36)], 1001–3000 [AOR = 9.7, 95% CI (3.45, 27.3)], and 3001–5000 [AOR = 6.56, 95% CI (1.96, 21.9)], working more than eight hours [AOR = 7.9, 95% CI (4.36, 14.64)], drinking alcohol [AOR = 3.28, 95% CI (1.63, 6.6)] and participants unsatisfied with their job [AOR = 3.12, 95% CI (1.36, 7.16)] were significantly associated with non-fatal occupational injury. The magnitude of non-fatal occupational injury among construction workers was high in the study area. The study concluded that sex, monthly income, length of working hours, drinking alcohol and dissatisfaction with job were risk factors for occupational injuries among construction employee.